Scripture Reading Urged Vehementer (DV NO. 25): Background and Development - Wicks, Jared (Theological studies, 2013)
This article relates the itinerary of Vatican II's exhortation to Catholics to practice prayerful Scripture reading. In 1961 the Preparatory Theological Commission treated Bible reading in a cautionary and admonitory mode that highlighted guidance by the Magisterium. But the Secretariat for Promoting Christian Unity insisted that pastoral ministers should introduce the faithful to devout reading of Scripture leading to personal encounters with God. The conciliar encouragement of lectio divina deserves appreciation and further application as a pastoral consequence of Vatican II's Dei verbum.